Analysis of People's Willingness to Use Personalization Services in Times of Disaster - Teppei Koguchi; Toshiya Jitsuzumi (International Telecommunications Society (ITS), 2018)
Japan has experienced major earthquake disasters in the past. The Great East Japan Earthquake of March 11, 2011 caused enormous damage. Subsequently, in April 2016, a major tremor centered in Kumamoto Prefecture in Kyushu also occurred. In the event of such a disaster, it is important to ensure that medical services are available and that a lifeline is secured. The use of information and communication technology, or ICT, is essential in implementing such efforts in an efficient manner. For example, ICT is very helpful in searching for evacuation routes, locating evacuation sites, tracking supply shortages, and understanding the situation at medical facilities. The use of ICT for such purposes requires personal information. Users can find their evacuation routes precisely because their locations are confirmed with GPS. People will also be able to locate medical facilities to receive special treatment if they register beforehand their pre-existing conditions. Thus, personal information utilization services are extremely effective in times of disaster. On the other hand, the use of personal information could raise concerns about privacy violations. While the use of personal information may allow for valuable services, privacy could be violated if data are leaked or handled in an inappropriate manner.
Keywords: L86; L96; 330